IRON DEFICIENCY ANEMIA IN PAKISTAN: CELIAC DISEASE AN UNDERLYING CAUSE - Khatoon, Shifaat; Ahmed, Aijaz; Yousaf, Shazia (Journal of Ayub Medical College Abbottabad, 2018)
Background: Iron deficiency anaemia (IDA) is common in Pakistani population and an important cause of morbidity. Celiac disease (CD) is an important contributor and its diagnosis is frequently missed especially if present in atypical/non-diarrheal form. Non-responders to iron replacement therapy typically raises suspicion of celiac disease as underlying cause. Aim of this study is to determine the frequency of CD in patients with IDA. Methods: A cross sectional study was conducted at tertiary health care centre Islamabad from 12th March to 12th September 2016. Two hundred & ninety patients of newly diagnosed IDA age more than 12 years, including both gender were selected trough non-probability purposive method. Patients with overt Blood loss (gastrointestinal, genitourinary, Pulmonary, recent Trauma or Surgery) were excluded. Active worm infestation and inadequate iron intake were also excluded. After informed consent, all the enrolled patients were investigated for presence of Anti-Tissue tansglutaminase antibody (Human Anti TTG IgA type) by ELISA in their serum at pathology laboratory of PIMS. Results: Out of 290 patients of IDA 32 (11%) had celiac disease (p=0.0002), more common in younger age <40 years 24 (75%), predominantly in female 22 (68.75%), more prevailing in Kashmiri population 9(28.12%). Conclusion: Celiac disease is common in patients who present with IDA. Diagnosis of CD is frequently missed in the absence of classic features and IDA may be the only manifestation of CD. Keywords: Celiac disease; Iron Deficiency anaemia; Celiac Serology; Anti endomyseal antibodies; Anti Tissue Trans glutamines antibodies